ИНДИКАТОР-САПРОБТЫ МИКРОБАЛДЫРЛАРДЫ ТАБИҒИ СУ ЭКОЖҮЙЕЛЕРІН БАҒАЛАУДА ПАЙДАЛАНУ (Experimental biology, 2015)
As a result of research algoflors of lake Zerenda 99 kinds of microseaweed are determined. The meaning of an index saprobe of lake Zerenda equal 1,98 proves, that waters of lake concern to - mezosaprob to a zone.
Keywords: lake Zerenda; microseaweed